Autres Dimensions : collages, assemblages, reliefs. - Galerie Beyeler, Basel (Basel : Galerie Beyeler, 1976)
Picasso, Pablo ; Braque, Georges ; Gris, Juan ; Severini, Gino ; Laurens, Henri ; Schwitters, Kurt ; Miró, Joan ; Arp, Jean ; Ernst, Max ; Klee, Paul ; de Staël, Nicolas ; Matisse, Henri ; Dubuffet, Jean ; Nicholson, Ben ; etc.
Autres Dimensions : collages, assemblages, reliefs, Galerie Beyeler, Basel, juin - septembre 1976
boek